2019
DOI: 10.3390/su11041068
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Phosphorus Release from Phosphate Rock Activated with Lignite by Mechanical Microcrystallization: Effects of Several Typical Grinding Parameters

Abstract: Recently, microcrystallization technology has gained much interest because of the enhanced dissolution of the target sample and promotion of the sustainable development of agriculture. Phosphorus (P) is one of the most important nutrients for increasing crop yield; the increase in effective P ratio directly from raw phosphate rock (PR) powder by mechanical grinding to increase its microcrystallinity is believed to be the best choice for this purpose. This study reports the improvement in the activation propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…6H), the phosphate ore powder particles were fine and rounded into a loose flocculent shape with blurred surface boundaries and disappearing angles. This shows that mechanical activation can promote more full contact between the active mineral and phosphate ore powder, which is conducive to improving the activation effect of the active mineral on phosphate ore powder (Zhang et al, 2019).…”
Section: Surface Morphological Changesmentioning
confidence: 86%
See 2 more Smart Citations
“…6H), the phosphate ore powder particles were fine and rounded into a loose flocculent shape with blurred surface boundaries and disappearing angles. This shows that mechanical activation can promote more full contact between the active mineral and phosphate ore powder, which is conducive to improving the activation effect of the active mineral on phosphate ore powder (Zhang et al, 2019).…”
Section: Surface Morphological Changesmentioning
confidence: 86%
“…Scanning electron microscope (SEM) analysis (Fig. 1) showed that the unactivated phosphate ore powder was mainly in the form of lumps of different sizes and irregular shapes, with dense structure, prominent angles, relatively good crystallinity, extremely easy to break, and good mechanical activation properties (Zhang et al, 2019;Laonapakul et al, 2021).…”
Section: Tested Phosphate Orementioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported improvements in the activation properties of PR with different lignite (as an activator) ratios (1%, 2%, 3%, and 5%) during the grinding process, to prepare for the microcrystallized PR. The dry matter of rapeseed and the soil-available P increased by 56.1% and 89.6%, respectively, with the direct use of PR and micro-crystallized PR in an aqui-cinnamon soil (pH 8.2), compared with the control test without the addition of phosphate minerals [18]. We proved that this was a feasible solution, with a 10-20% substitution of MAPR for P fertilizer on spring maize in the Northeast China for nearly neutral soil (pH 6.47).…”
Section: Introductionmentioning
confidence: 92%
“…In this context, numerous co-application techniques have been proposed in the literature, such as the addition of biomasses [22][23][24][25], microorganisms [26][27][28], and inorganic substances to agricultural soils [29][30][31][32]. However, many of the proposed solutions are complex and expensive, limiting their practical application at the field level.…”
Section: Introductionmentioning
confidence: 99%